CLASSIFICATION, DISTRIBUTION AND PRODUCTION OF KNOWLEDGE: THEORETICAL SUMMARY - R. A. Tchupin (Образование и наука)
The paper is devoted to systemizing the main theoretical approaches to classification, distribution and production of knowledge in the global economy. The author focuses on F. Machlup’s knowledge classification and the concept of useful knowledge by J. Mokyr.The interpersonal and public channels of communication and acquisition of knowledge are observed taking into consideration the total changes caused by transition from industrial to postindustrial economy. The paper provides a comparative analysis of the given model and alternative concepts of knowledge generation: finalization of science, strategic research, post-normal science, academic capitalism, post-academic science, and the triple helix concept. The author maintains that the current concepts of knowledge generation reflect the fact of transformation of modern institutional technical environment due to the global technological changes, and increasing contribution of knowledge to the economic development. Accordingly, the roles of the main participants of the given process are changing along with the growing integration of education and science, state and businesses.